A rare presentation of exudative macroaneurysms in unilateral Eales’ disease - Nada, M; Qanoongo, S; Singh, SV; Khurana, AK (Nepalese Journal of Ophthalmology, 2017)
Background: A case of exudative macroaneurysms in unilateral Eales’ disease is reported. ‘Eales disease’ is an idiopathic bilateral occlusive periphlebitis with neovascularisation and mostly presents with vitreous hemorrhage. Case: A 30 year old male presented with diminution of vision in left eye (6/36) for 1 month. Slit Lamp examination of both eyes revealed normal anterior segment. Fundus examination of left eye with + 90 D lens revealed reddish lesions at the macula with surrounding circinate exudation. On peripheral examination hemorrhages were seen along with vasculitis in the superotemporal quadrant.The right eye fundus was normal.All laboratory investigations were found within normal limits. Conclusion: Eales’ disease is mostly a bilateral condition but this case is rare as there is uniocular involvement with exudative macroaneurysms.Laser therapy was instituted which was effective in management of this condition with restoration of normal visual acuity.There was no relapse on follow up for 2 years.